Hara Tanzan and the Japanese Buddhist discovery of “Experience” - Licha, Stephan (Journal of Religion in Japan, 2021)
Abstract This paper explores the role of Hara Tanzan 原坦山 (1819–1892) in the transformation of Buddhism into an “experiential religion” during the Meiji period. Scholars such as Sharf have argued that this transformation is due to Western influence on figures such as DT Suzuki. Japanese language scholarship has instead shown that in the early 1900s, the notion of Buddhism as experiential religion was already widespread, considering Tanzan as a predecessor of this discourse. I argue that Tanzan was among the first to discover the importance of “experience” in the confrontation with science, yet interpreted it as an empirical standard for both religious and scientific knowledge. However, Tanzan did not yet establish the separation of science and religion characteristic of the modern understanding of both terms. I conclude that Tanzan was one starting point in a dialectic that is integral to the indigenous genealogy of “religious experience” in Japan.